Macrophage-tregs crosstalk: the “hub” of the immune network in MASLD - Zhao, Huihui; Wang, Weili; Zhu, Pengchao; Shi, Zhaohong (Frontiers in Immunology, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is a globally prevalent metabolic disorder with a high average worldwide prevalence. It occurs more frequently in men than in women, and its incidence increases with age. MASLD can progressively advance to liver fibrosis, cirrhosis, and even hepatocellular carcinoma, while also elevating the risk of cardiovascular, renal, and other systemic diseases. Its pathological progression is closely associated with dysregulation of the hepatic immune microenvironment, in which aberrant crosstalk between Macrophages (Mø) and regulatory T cells (Tregs) serves as a central driving mechanism. Under physiological conditions, liver-resident Macrophages (Kupffer cells, KCs) and Tregs maintain immune homeostasis through a “complementary origin–spatial co-localization-molecular crosstalk” mechanism. In MASLD, KCs numbers decline while monocyte-derived Macrophages (MDMs) are abnormally recruited, giving rise to Macrophages with distinct phenotypes. Tregs influence the classical phenotypic differentiation of Macrophages. However, dynamic alterations in Treg abundance exhibit a “double-edged sword” effect. The disrupted crosstalk between KCs and Tregs involves dysregulated chemokine networks [e.g., c-x-c motif chemokine ligand 9 (CXCL9), c-c motif chemokine ligand 2 (CCL2)], cytokine interactions [e.g., interleukin-1β (IL-1β), transforming growth factor- Beta (TGF-β)], and signaling pathways such as beta-catenin (β-catenin) and notch homolog 1 (Notch1). Collectively, these alterations drive disease progression from steatosis to hepatitis and fibrosis. This review systematically summarizes the physiological mechanisms underlying Macrophages -Tregs crosstalk, its pathological dysregulation in MASLD, and the associated molecular networks, while proposing targeted therapeutic strategies based on disease stage.